Return to sport after isolated meniscal repair in amateur athletes – factors influencing successful recovery: narrative review - Żabicki, Michał; Bajorek, Julia; Gąsiorek, Natalie; Kuźnar, Anna; Gruchot, Hanna (Quality in Sport, 2026)
Background. Meniscal injuries are common among physically active individuals and amateur athletes, particularly in sports involving pivoting movements and rapid changes of direction. Preservation of the meniscus has become increasingly important due to its biomechanical role and the risk of degenerative joint changes after meniscectomy. Return to sport (RTS) is one of the primary goals of treatment. Aim. To analyse current evidence regarding factors influencing RTS after isolated meniscal repair in amateur athletes. Material and methods. This narrative review was based on literature available in PubMed, Scopus, and Google Scholar databases published between 2015 and 2025. Original studies, systematic reviews, retrospective studies, and narrative reviews concerning isolated meniscal repair, rehabilitation, and RTS were included. Results. Successful RTS after isolated meniscal repair depends on multiple factors. Younger age, peripheral tears located in vascularised zones, and longitudinal tear patterns are associated with better healing and improved functional outcomes. Rehabilitation, restoration of quadriceps strength, proprioception, and dynamic knee stability play a crucial role in recovery. Psychological factors, including fear of reinjury and confidence, may also affect RTS outcomes. Most studies report high RTS rates, although not all patients return to their preinjury level of activity. Conclusions. Isolated meniscal repair enables successful RTS in most amateur athletes while preserving knee biomechanics. Rehabilitation and patient-related factors remain key determinants of postoperative outcomes. Further prospective studies with standardised RTS criteria are needed.